Pengaruh Green Marketing, Pengetahuan, Inovasi Produk terhadap Minat Beli dan Keputusan Pembelian - Moh Ali Khomsin; Mochamad Edris; Joko Utomo (Penerbit Goodwood, 2022)
Purpose: Analyzing the influence of green marketing, product knowledge and innovation on buying interest and purchasing decisions. Methodology: Research location at Indomaret in Jati District, Kudus Regency, explanatory research, AMOS SEM data analysis 24, 5 variables, 32 indicators observed by questionnaire, 160 respondents, accidental sampling technique. Results: Green marketing has a positive effect on purchasing decisions. Product knowledge has a positive effect on purchasing decisions. Product innovation has a positive effect on purchasing decisions. Green marketing has a positive effect on purchase intention. Product knowledge has a positive effect on interest in buying products. Product innovation has a positive effect on purchase intention. Buying interest has a positive effect on purchasing decisions. Green marketing has a positive effect on purchasing decisions through buying interest. Product knowledge has a positive effect on purchasing decisions through purchase intention. Product innovation has a positive effect on purchasing decisions through buying interest. Limitations: Research only with three exponential variables, two endogenous variables, buying interest as an intervening variable. And only in Indomaret in Jati District, Kudus Regency. Contribution: The research results strengthen the Theory of Planned Behavior (TPB), strengthen the results of previous research. This is a new finding, namely that there is a positive influence between product innovation and purchasing decisions through buying interest. Regarding green marketing, it is hoped that there will be an increase/addition of Indomaret AMDK products that are healthy, quality, and environmentally friendly.